Dynamic modulation of genomic enhancer elements in the suprachiasmatic nucleus, the site of the mammalian circadian clock - Bafna, Akanksha; Banks, Gareth; Hastings, Michael H.; Nolan, Patrick M. (Genome Research, 2023)
The mammalian suprachiasmatic nucleus (SCN), located in the ventral hypothalamus, synchronizes and maintains daily cellular and physiological rhythms across the body, in accordance with environmental and visceral cues. Consequently, the systematic regulation of spatiotemporal gene transcription in the SCN is vital for daily timekeeping. So far, the regulatory elements assisting circadian gene transcription have only been studied in peripheral tissues, lacking the critical neuronal dimension intrinsic to the role of the SCN as central brain pacemaker. By using histone-ChIP-seq, we identified SCN-enriched gene regulatory elements that associated with temporal gene expression. Based on tissue-specific H3K27ac and H3K4me3 marks, we successfully produced the first-ever SCN gene-regulatory map. We found that a large majority of SCN enhancers not only show robust 24-h rhythmic modulation in H3K27ac occupancy, peaking at distinct times of day, but also possess canonical E-box (CACGTG) motifs potentially influencing downstream cycling gene expression. To establish enhancer–gene relationships in the SCN, we conducted directional RNA-seq at six distinct times across the day and night, and studied the association between dynamically changing histone acetylation and gene transcript levels. About 35% of the cycling H3K27ac sites were found adjacent to rhythmic gene transcripts, often preceding the rise in mRNA levels. We also noted that enhancers encompass noncoding, actively transcribing enhancer RNAs (eRNAs) in the SCN, which in turn oscillate, along with cyclic histone acetylation, and correlate with rhythmic gene transcription. Taken together, these findings shed light on genome-wide pretranscriptional regulation operative in the central clock that confers its precise and robust oscillation necessary to orchestrate daily timekeeping in mammals.
10.1101/gr.277581.122